Urbanized landscapes in early Syro-Mesopotamia and prehispanic Mesoamerica : papers of a cross-cultural seminar held in honor of Robert McCormick Adams - Domenici, Davide; Marchetti, Nicolò; Adams, Robert McC (2018)
Meant as a homage to the memory of Robert McCormick Adams and born out of a conference organized at the University of Bologna to celebrate the fiftieth anniversary of the publication of his book The Evolution of Urban Society: Early Mesopotamia and Prehispanic Mexico(1966), the volume brings together contributions by scholars tackling ancient urbanism from different regions and theoretical perspectives aiming at providing elements that could enhance cross-cultural dialogue and cross-fertilization between various theoretical and methodological approaches.